Sustainable Superhydrophobic Paper-Based Materials with Tunable Wettability via Olive Oil-Assisted Deposition - Peker, Defne; Boga, Zeynep; Kantepe, Zehra Sude; Sagir, Kadir; Kurtoglu-Oztulum, Samira F.; Kosak Soz, Cagla (AMER CHEMICAL SOC, 2026)
The increasing demand for sustainable water-repellent materials has intensified interest in environmentally benign alternatives to conventional polymer-coated paper for packaging applications. Superhydrophobic paper-based materials were fabricated from sustainable and earth-abundant precursors, olive oil (OO), fumed silica (N20), and sepiolite (SEP), with the aim of achieving durable superhydrophobicity using minimal material input via spray-coating and transesterification. This approach enables extreme water repellency on cellulose-based substrates while maintaining sustainability and a minimal coating thickness. The micrometer-thick coatings minimized material consumption and led to a gradual increase in the water contact angle, rising from 0 degrees for pristine Whatman grade 1 filter paper (WFP) to 123.7 +/- 1.4 degrees (WFP/OO), 144.6 +/- 2.8 degrees (WFP/OO/N20), and 150.9 +/- 2.6 degrees (WFP/OO/SEP), ultimately reaching a superhydrophobic state of 159.6 +/- 2.5 degrees with a contact angle hysteresis of 4.0 +/- 2.6 degrees for the hybrid WFP/OO/SEP/N20 formulation. The resulting superhydrophobic surfaces exhibit an effective physical self-cleaning capability while preserving the breathability of the paper-based substrate. Scanning electron microscopy (SEM) revealed the formation of hierarchical micro/nanoscale surface roughness, which is commonly associated with superhydrophobic behavior, while attenuated total reflectance Fourier-transform infrared (ATR-FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) confirmed anchoring of the coating components onto the cellulose surface. In addition, a 10-fold increase in the wet tensile index was observed for the superhydrophobic paper compared to pristine WFP. These results demonstrate that the synergistic combination of olive oil and inorganic particles enables the fabrication of high-performance superhydrophobic paper without fluorinated compounds or synthetic polymers. Overall, integrating paper with inorganic particles and olive oil provides a scalable and sustainable alternative to conventional fossil-based polymer-coated paper composites for advanced packaging applications.
Keywords: CELLULOSE; SURFACES; XPS; Chemistry; Materials Science